Pendampingan Pelaksanaan Program Warung Stop Stunting di Kelurahan Klegen dan Manisrejo Kota Madiun - Marsana; Danik Karyawati; Supriyatun (JURNAL DAYA-MAS, 2024)
The Madiun City Government officially launched the Stop Stunting Warung (WSS) program. WSS is present in every sub-district as a form of building complete human beings to realize community welfare. The program runs for 9 weeks starting on Tuesday, October 18, 2022, and ending on Tuesday, December 26, 2022, targeting pregnant women and toddlers in all 27 neighborhoods across 3 districts of Madiun City. In this program, pregnant women and stunted children will receive a weekly Social Package consisting of; 1) Staple foods such as rice, eggs, canned fish, milk, oil, biscuits, vegetables, and fruits; 2) Ready-to-eat Lunch; 3) Shopping Vouchers worth Rp. 50,000. Tantular Cooperative Management Academy strongly supports and highly appreciates this program by joining as an implementing partner in two neighborhoods, namely Klegen and Manisrejo. The program is expected to realize a healthy, intelligent, and morally upright Madiun community.